FAM83G/Fam83g genetic variants affect canine and murine hair formation. Issue 4 (3rd August 2018) - Balmer, Pierre; Fellay, Auxanne K.; Sayar, Beyza S.; Hariton, William V. J.; Wiener, Dominique J.; Galichet, Arnaud; Müller, Eliane J.; Roosje, Petra J.
Abstract: FAM83G/Fam83g genetic variants have been described in dogs, mice and recently also in humans. They are associated with palmoplantar keratoderma and altered hair or coat phenotype, reported as wooly phenotype in mice. FAM83G/Fam83g is an unexplored effector of temporally and spatially coordinated Wnt and BMP signalling which are key pathways in pre‐ and postnatal hair follicle morphogenesis and differentiation. The aim of this study was to unravel phenotypic consequences of FAM83G/Fam83g variants on hair coat formation in dogs and mice. Our results show differences in hair types and hair shaft structures in both species. Additionally, mice exhibit deregulated hair cycle progression which timely correlates with defective Wnt signalling (Axin2) and Bmp2/4 expression. These results affirm the involvement of FAM83G in hair morphogenesis, hair follicle differentiation and cycling.